2019
DOI: 10.1177/0734242x19842328
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging recycling among households in Malaysia: Does deterrence matter?

Abstract: To encourage recycling in Malaysian households, a waste separation at source programme was implemented that made it mandatory for households to sort their waste into different categories before leaving it out for collection. Penalties designed to act as a deterrent are imposed on households that fail to sort their waste appropriately. But does this deterrence motivate compliance with the programme directives? This study employs the deterrence theory to investigate if deterrence alone is sufficient to motivate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…The introduction of penalties or 'pay as you throw' may increase incidents of waste fly-tipping or dumping in public places to avoid paying for waste disposal. In contrast, Ogiri et al (2019) in their study of using a deterrence approach to nudge citizens to carry out recycling activities found that the introduction of negative incentives in form of fines and sanctions was a substantial factor in increasing residents' participation in recycling activities. Similarly, the plastic bag tax introduced in the United Kingdom has cut down the rate of plastic bag usage; the latest data published by DEFRA indicate an 85-95% reduction in the use of plastic bags, in the United Kingdom, between 2018 and 2020 (DEFRA, 2020c).…”
Section: Outcomementioning
confidence: 96%
“…The introduction of penalties or 'pay as you throw' may increase incidents of waste fly-tipping or dumping in public places to avoid paying for waste disposal. In contrast, Ogiri et al (2019) in their study of using a deterrence approach to nudge citizens to carry out recycling activities found that the introduction of negative incentives in form of fines and sanctions was a substantial factor in increasing residents' participation in recycling activities. Similarly, the plastic bag tax introduced in the United Kingdom has cut down the rate of plastic bag usage; the latest data published by DEFRA indicate an 85-95% reduction in the use of plastic bags, in the United Kingdom, between 2018 and 2020 (DEFRA, 2020c).…”
Section: Outcomementioning
confidence: 96%
“…A good campaign should include a persuasive approach with various aspects to attract community attention. Nevertheless, some study has stated that participation from the community in waste segregation is still low even though much public awareness has been conducted through the years [31]. Moreover, marketing mediums such as posters, pamphlets, advertisements on television, radio, websites, billboards, and others do not significantly impact waste segregation behaviour [28].…”
Section: Methods That Can Encourage Waste Segregationmentioning
confidence: 99%
“…Mandatory policies refer to the rules governing behavior, and policymakers design a package of commonly agreed standards, penalties, supervision, and enforcement when mandates are used [35,36]. Previous studies suggest that mandatory policies play key roles in promoting waste separation [20,[37][38][39]. For instance, in July 2019, Shanghai took the lead in formulating and implementing a mandatory waste separation policy via supervisory guidance, penalties, regulated disposal times, and others [40], and its waste separation rate increased from 15% to 80% [41].…”
Section: Waste Separation Policiesmentioning
confidence: 99%